2015
DOI: 10.1089/dia.2014.0308
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Role of Social Network Sites in the Treatment of Adolescent Diabetes

Abstract: Of all the forms of social media, social network sites (SNS) have seen the fastest and broadest uptake, and their role within health care is only starting to be explored. SNS in clinical practice have the potential to provide education and support without the costs and constraints of more conventional treatment approaches. However, in order to effectively utilize SNS, it is important to use the SNS most frequented by adolescents. Despite the increase in the use of SNS in diabetes management, there are very few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…For example, Sun and colleagues [40] demonstrate in their study that the effectiveness of mobile applications differs between type 1 and type 2. Furthermore, the multitude of definitions regarding 'distal' technologies vary considerably and while some studies show an improvement in HL, others show no significant improvement [30][31][32]. Additionally, 'distal' digital tools are used for secondary prevention and not primary prevention, as is the case for 'proximal' digital tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Sun and colleagues [40] demonstrate in their study that the effectiveness of mobile applications differs between type 1 and type 2. Furthermore, the multitude of definitions regarding 'distal' technologies vary considerably and while some studies show an improvement in HL, others show no significant improvement [30][31][32]. Additionally, 'distal' digital tools are used for secondary prevention and not primary prevention, as is the case for 'proximal' digital tools.…”
Section: Discussionmentioning
confidence: 99%
“…The Critical Appraisal Skills Programme (CASP) tool was used for quality appraisal in qualitative evidence synthesis in six studies [12,24,27,28,31,32]. The CASP tool does not produce results classified as overall 'high' , 'medium' or 'low' quality [38].…”
Section: Risk Of Bias In Studiesmentioning
confidence: 99%
“…This is concerning as research has shown a relationship between comparison in social media and poor mental health [290]. Furthermore, there can be misleading information on social media about diabetes and health [291], which could potentially be harmful to self-care in youth.…”
Section: Using Smartphone Apps and Phone-based Systems To Improve T1dmentioning
confidence: 99%
“…Over the last decade, the use of social media has increased significantly and integrated into many aspects of our work and personal lives . Currently, there are approximately 1.96 billion social network users in the world, which is projected to increase to 2.44 billion by the year 2018 .…”
mentioning
confidence: 99%
“…Currently, there are approximately 1.96 billion social network users in the world, which is projected to increase to 2.44 billion by the year 2018 . Social media is a potential mechanism for communication of health information as it is provided free of cost and is highly accessible for information to patients . Amongst all the social networking sites (SNSs), the most extraordinary expansion has been noted in Facebook, with the fastest and the most constant growth .…”
mentioning
confidence: 99%